NASM Essentials of Personal Fitness Training /. - Lucett, Scott C., ....-; Sutton, Brian G., ....- (Burlington : Jones & Bartlett Learning, 2018)
Pursue. Transform. Inspire. Gain the information, insight, and inspiration you need to change the world as a fitness professional. You'll also learn the foundations of exercise science, fitness assessments, nutrition, and how to grow a personal training business. Since 1987, the National Academy of Sports Medicine (NASM) has been a global leader in providing evidence-based certification and specializations. NASM Essentials of Personal Fitness Training, Sixth Edition, continues to lead the way by providing the most comprehensive resource for aspiring personal trainers, health and fitness professionals and enthusiasts. Through NASM's proprietary Optimum Performance Training (OPTTM) model, this text will teach you a systematic approach for designing exercise programs that can help anyone reach their fitness goals. Reader-friendly content includes: - NEW NASM-CPT Exam Prep Content provides Quick Check Concepts, test taking best practices, as well as updated science relevant to the personal trainer - Protocols for building stabilization, strength, and power program - Exercise techniques, purpose, and safety tips - Key definitions bolded and defined - Stretch Your Knowledge boxes emphasizing major concepts and current research - Memory Joggers highlighting concepts and program design instructions - Chapter Summaries with key point reminders - Extensive full-color images and charts - Plus you'll get over 100 additional exercises; OPT workout programs; one repetition maximum conversion chart; and a muscle origin, insertion, and function guide
Keywords: Krachttraining